'Extenuating circumstances' in the South African law of murder - Evans, Stanley (Institute of Criminology, 2023)
The concept of statutory "extenuating circumstances" was' introduced into the South African criminal law of murder. 1935 in _tile use of those two words alone. It was left to the course, without any further legislative aid, to provide the definition, structure, and development of the concept. Over the· period of more than forty years there has been), ·no -written attempt to survey or deal at any length this development. Beside legal textbooks which give some brief rough grouping of certain of the cases . I (E.M PM A Hunt, South African Criminal law and procedure, Volume II allo6ates ten pages - the most detailed textbook handling of the matter so far there have been two , -c ' articles 1.n law journals ( one by ,the present writer in 195·5 and Loubser in 1977) which have attempted a form· 9f analysis or development of the subject. This thesis is in the nature of, pilot study along a certain line approach in an attempt to order the appropriate material. No entry has been made into the discussion of the substantive legal concepts in the law of murder or any ease of contention there, even though these may have been referred to in passing. Rather have the generally accepted '/ statements of the substantive law been accepted. What i's sough to be dealt with is the limited area of the relevance application of certain considerations appropriate only to the :sentencing function in cases where an accused is found guilty: if murder in South Africa. But even this limited·· .ficid of study has a dynamic broadness about it which ass6ciates with other disciplines such as ethics, anthropology, psychiatry and other psycho-social sciences.